Komunikasi Pembangunan Berbasis Literasi Digital: Kerangka Konseptual Pemberdayaan Kelompok Wanita Tani dalam Pengembangan Desa Wisata Brongkol, Cangkringan Sleman - Nina Kusumawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Digital transformation has reshaped development communication by expanding access to information and strengthening community participation. However, digital literacy disparities remain a major challenge in rural areas, particularly among women who often face limited access to and productive use of digital technologies. In Indonesia, Women Farmers Groups (Kelompok Wanita Tani—KWT) play a strategic role in supporting food security, local economic empowerment, and community-based tourism development. Nevertheless, most empowerment programs continue to emphasize agricultural production and business capacity while paying insufficient attention to development communication supported by digital literacy. Furthermore, previous studies have generally examined digital literacy, women's empowerment, and rural tourism as separate topics, leaving limited conceptual integration among these perspectives. This conceptual paper aims to develop a development communication framework based on digital literacy to empower Women Farmers Groups in supporting the sustainable development of Brongkol Tourism Village, Sleman Regency. The study adopts a qualitative conceptual approach through an extensive literature review of scholarly articles, academic books, government policy documents, and reports from international organizations. The conceptual synthesis integrates Development Communication Theory, Diffusion of Innovations Theory, Digital Divide Theory, and UNESCO's Digital Literacy Global Framework. The proposed framework positions participatory development communication as the central mechanism for enhancing digital competencies through collaborative learning, knowledge sharing, digital content creation, and strategic use of digital media. Strengthened digital literacy is expected to improve the communication capacity of Women Farmers Groups, expand market access for local products, enhance tourism promotion, and increase women's participation in sustainable rural development. The proposed framework contributes to the literature by integrating development communication, digital literacy, women's empowerment, and community-based tourism into a comprehensive conceptual model that can guide the design of more inclusive and sustainable digital empowerment programs in rural communities.